An investigation into ‘community expectations’ surrounding animal welfare law enforcement in Australia - Morton, Rochelle; Hebart, Michelle L.; Ankeny, Rachel A.; Whittaker, Alexandra L. (Frontiers in Animal Science, 2022)
Nature of reform to animal welfare legislation in Australia has commonly been attributed to increasing alignment with the ‘communities’ expectations’, implying that the community has power in driving legislative change. Yet, despite this assertion there has been no publicly available information disclosing the nature of these ‘expectations’, or the methodology used to determine public stance. However, based on previous sociological research, as well as legal reforms that have taken place to increase maximum penalties for animal welfare offences, it is probable that the community expects harsher penalties for offences. Using representative sampling of the Australian public, this study provides an assessment of current community expectations of animal welfare law enforcement. A total of 2152 individuals participated in the survey. There was strong support for sentences for animal cruelty being higher in magnitude (50% support). However, a large proportion (84%) were in favour of alternate penalties such as prohibiting offenders from owning animals in the future. There was also a belief that current prosecution rates were too low with 79.6% of respondents agreeing to this assertion. Collectively, this suggests a greater support for preventing animal cruelty through a stronger enforcement model rather than punishing animal cruelty offenders through harsher sentences. This potentially indicates a shift in public opinion towards a more proactive approach to animal welfare, rather than a reactive approach to animal cruelty.